Promoting adherence in adolescents and young adults with cancer to optimize outcomes: A developmentally oriented narrative review. Issue 4 (30th December 2019) - Vandermorris, Ashley; Sampson, Lorna; Korenblum, Chana
Abstract: Adherence is a critical consideration in ongoing efforts to improve outcomes among adolescents and young adults (AYAs) with cancer. In this narrative review, we embed existing conceptualizations of adherence within a developmental context to provide a novel vantage point from which to examine this important issue. Applying this developmentally oriented framework, we summarize the most current literature on strategies to enhance adherence in the AYA population. A developmentally informed approach to working with AYAs can elucidate unique strengths and vulnerabilities of this population and offer a new perspective on opportunities to respond to biopsychosocial barriers to adherence in a strengths‐based, collaborative manner.